Surgery-First Technique for a Patient with Major β-Thalassemia - Soleimani, Milad; Behnaz, Mohammad (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: Thalassemic patients commonly present malocclusions, which require both orthognathic treatments and surgury. This study aimed to assess prioritizing the surgery over orthodontic treatment. Case report: Surgery-first method was performed to treat severe gummy smile and mild retrognathic mandible and prognathic maxilla in a 24-year-old Iranian girl with major β-thalassemia. Brackets and Ni-Ti wires were adjusted on all teeth to align their levels for one month. Then, the patient underwent the surgery, and the soft tissue was excised for Lefort dissection by two cutting lines, followed by osteotomy. Afterwards, down fracture and bilateral septoplasty were carried out, and excessive bones were removed. The surgery retruded the maxilla by 10 mm. Results: The 2-year follow-up revealed no overgrowth of the maxilla or malocclusion. Conclusion: Surgery-first method can be successfully used for treatment of malocclusions in patients with major thalassemia.